INHIBITION MOTORA EN LA CORTEZA CEREBRAL - ALCALDE OBRADOR, S (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1945)
The use of a Ag staining technique demonstrates intercellular outlines in the thyroid epithelium The outlines vary somewhat for different types of epithelium but exhibit, generally, a wedge shape base fitting over the follicle and an elongation of varyin
BOL INST ESTUD MED BIOL
Keywords: INHIBITION, MOTORA, CORTEZA, CEREBRAL; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA